THE NATIVE CULTURES ON STUDENT DISCIPLINE IN SCHOOL, NIGERIA - Edewor Ogwu (SCAD Independent, 2016)
Students discipline problem is developing into an epidemic in Nigerian schools. Every culture has its own values and norms, and these are communicated to its young generation through disciplinary strategies; and being culturally conceptualized and negotiated, these strategies and the languages therein, can only be understood by the members of the identifiable cultural group. The study evaluates some relevant information on teachers’ routine experiences and their views on the effectiveness the enforcement of order, control and disciplinary actions in secondary schools and how school disciplines are influenced by the cultural background of the Staff and students. This study explores teachers’ views on the common approaches and school disciplinary models in Nigeria. The paper suggests that the current educational administration and policies erodes the powers of the secondary Staff to such degree that teachers are disempowered hence, indiscipline among students continues to gather momentum causing poor academic performances.